Estudo clínico, randomizado, controlado por placebo do efeito da suplementação de açaí em marcadores associados ao zumbido crônico - Oppitz, Sheila Jacques (2020)
Introduction: Chronic tinnitus is a subjective multifactorial symptom, in which different treatments are proposed for its management, antioxidants have been shown as an apparently promising perspective. Açaí extract, made of an Amazon native fruit, has an anti-inflammatory and antioxidant capacity, capable of preventing and reducing diseases, being usually somehow associated with tinnitus. Aim: Verifying the effectiveness of the experimental treatment, açaí extract with everyday supplementation, to decrease the discomfort of chronic tinnitus, comparing its effect isolated and associated to speech therapy counseling in a single session and understanding the mechanisms related to the oxidative metabolism of this population. Methodology: A randomized, placebo-controlled clinical trial was carried out with three groups: Placebo Group (starch capsules), Açaí Group (capsules with 100mg of açaí dry extract) and Açaí Group associated with Counseling (100mg of açaí and counseling in one session). The data obtained in the Tinnitus Investigation Anamnesis served as support to identify the symptomatological aspects and health conditions, evaluated with the following procedures in the evaluation and after three months of treatment: Visual Analogue Scale (VAS), Minimum Masking Level (MML), Tinnitus Handicap Inventory (THI), Beck Anxiety Inventory, The World Health Organization Quality of Life and oxidative stress biomarkers (Dichlorofluoresceinadiacetate, Lipid Peroxidation, Protein Carbonylation). Results: 45 subjects participated of this study, with a mean age of 52.9 years, 19 males and 26 females, with normal hearing thresholds or sensorineural hearing loss to a mild degree. There was a decrease in the discomfort with tinnitus at the moment after treatment, for the groups that used açaí supplementation, isolated açaí (VAS p = 0.006; THI p = 0.006), açaí associated with Counseling (VAS p = 0.002; THI p = 0.014). Placebo group decreased anxiety scores (p = 0.017) and MML (p = 0.013). There were no statistically significant differences for quality of life and oxidative stress biomarkers. Conclusion: The oral antioxidant supplementation, made of açaí extract, proved to be beneficial to reduce discomfort with chronic tinnitus, either isolated or with speech therapy counseling, regardless of the underlying etiology and it acan be considered as a treatment modality. In addition, monthly follow-up, without supplementation, helped to alleviate anxiety, improving symptom masking levels. However, the effect of this supplementation on oxidative stress biomarkers needs further investigation.